ACTUAL PROBLEMS OF IMPLEMENTING ECDL COURSE IN THE TRAINING OF TEACHERS - Petuhova, Л.Є.; Osipova, H.B.; Kushnir, H.O. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with actual problems of providing training for future teachers in line with international standards in the ICT field, the experience of creating an Internet portal ECDL e-learning for higher education in the KSU, and the organization of a distance course by tools of platform MOODLE.